Prazer e sofrimento no processo de formação de residentes multiprofissionais de saúde - Fernandes, Marcelo Nunes da Silva (2013)
This study aims to identify the perceptions of residents multidisciplinary health on situations of pleasure and suffering in the process of formation and characterize them sóciodemograficamente. For the basis of this study we adopted the theoretical framework of psychodynamics of work in perspective Dejours. Nine subjects participated in the study who worked in the Integrated Multidisciplinary Residency Programs in Public Health System, Federal University of Santa Maria. Self-administered sociodemographic data and focus group, which totaled three sessions and occurred in April 2013, taking into account the objectives of the study structured questionnaire: two instruments for data collection were used. For the treatment of sociodemographic data Simple descriptive statistics were used and qualitative data collected through the focus groups, content analysis proposed by Bardin was performed. In the focus group sessions categories which covered situations of pleasure and suffering in the process of training of residents, especially the structure and organization of the residence and its interface with the multidisciplinary approach emerged. This study met the Resolution Nº. 196/96 of the National Health Council Regarding sociodemographic results most are female, aged between 22 and 45, higher education, length of service less than a year and approved in the first selection process. Most residents had as a reason for admission to one of Residency Programs the opportunity to acquire knowledge related to health. As regards the situations of pleasure in the training of residents multidisciplinary health-related structure and organization of such Residence proceedings relate to the possibilities of learning with different areas of expertise, sharing knowledge and recognition and professional gratification user. Suffering is evidenced by work overload, the difficulty of understanding the methodology, teaching classes and linkage for the transmission of content, the extensive workload, lack of understanding of the meaning of theoretical concepts and their absence in the working practices of teams health. Regarding the situations of pleasure with the multidisciplinary approach of the Residence, the study reveals that, for the residents of multidisciplinary health, these are due to the development of multicharacter actions. Suffering is related to negative feelings conveyed by workers of health services, demotivation of preceptors and mentors, lack of recognition, the difficulties of integrating the different areas of emphasis of the Residence, the difficulties to participate in other educational activities, actions bureaucratized of Housing Programs, the idea of hand labor and mental suffering. Soon, with the grounding assumptions psychodynamics of work, it is suggested initiatives that can help to overcome the painful situations, such as: the creation of formal spaces for discussion of proposals and exchanges of experiences between and Residency Programs health services, the building shared among health care workers and residents of the matricial multidisciplinary health and natural therapeutic project, the construction of user-centered interventions and recovery of multidisciplinary health residents as active subjects in the teaching-learning process.